Collaboration of 3D context and extracellular matrix in the development of glioma stemness in a 3D model. (February 2016) - Ma, Nina K.L.; Lim, Jia Kai; Leong, Meng Fatt; Sandanaraj, Edwin; Ang, Beng Ti; Tang, Carol; Wan, Andrew C.A.
Abstract: A hierarchy of cellular stemness exists in certain cancers, and any successful strategy to treat such cancers would have to eliminate the self-renewing tumor-initiating cells at the apex of the hierarchy. The cellular microenvironment, in particular the extracellular matrix (ECM), is believed to have a role in regulating stemness. In this work, U251 glioblastoma cells are cultured on electrospun polystyrene (ESPS) scaffolds coated with an array of 7 laminin isoforms to provide a 3D model for stem cell-related genes and proteins expression studies. We observed collaboration between 3D context and laminins in promoting glioma stemness. Depending on the laminin isoform presented, U251 cells cultured on ESPS scaffolds (3D) exhibited increased expression of stemness markers compared to those cultured on tissue culture polystyrene (2D). Our results indicate the influence of 3D (versus 2D) context on integrin expression, specifically, the upregulation of the laminin-binding integrins alpha 6 and beta 4. By a colony forming assay, we showed enhanced clonogenicity of cells grown on ESPS scaffolds in collaboration with laminins 411, 421, 511 and 521. Evaluation of patient glioma databases demonstrated significant enrichment of integrin and ECM pathway networks in tumors of worse prognosis, consistent with our observations. The present results demonstrate how 3D versus 2D context profoundly affects ECM signaling, leading to stemness.